ï¡ - C-Compactness - Esmaeel, R. B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduce a new type of compactness which is called "ï¡-ccompactness". Also, we study some properties of this type of compactness and the relationships among it and compactness, ï¡-compactness and c-compactness